Smurf2 regulates IL17RB by proteasomal degradation of its novel binding partner DAZAP2 - Popova, Anna; Kzhyshkowska, Julia; Nurgazieva, Dinara; Goerdt, Sergij; Gratchev, Alexei (Immunobiology, 2012)
IL17RB is the receptor for IL17E, the only member of IL17 family promoting Th2 reactions. The mechanism of IL17BR regulation is poorly understood. We previously demonstrated that expression of IL17RB is induced on human macrophages by IL4 and enhanced by TGFβ. In the present study we investigated the immediate signaling targets of IL17RB. Using Yeast Two Hybrid screening we identified DAZAP2 as a binding partner of IL17RB. We established that 2 SH2-binding domains of DAZAP2 are essential for its binding to IL17RB. Deletion of these domains or substitution of tyrosines to alanines abrogates the binding. In IL17RB DAZAP2-binding domain was mapped to the region between aa 329 and 347 within its cytoplasmic part. Confocal microscopy revealed that in primary human macrophages that do not express IL17RB DAZAP2 is predominantly localized in the nucleus, while in IL17RB positive macrophages a portion of DAZAP2 is visualized in the cytoplasm. Stimulation of IL17RB with its ligand IL17E induces accumulation of DAZAP2 in the cytoplasm. Further we established that DAZAP2 interacts with Smurf2 an E3 ubiquitin ligase which induces proteasome-dependent degradation of the protein. In summary we established a new mechanism of IL17RB regulation-Smurf2 dependent degradation of its adaptor protein DAZAP2.